Principles of Research Framework and Methodology: A Critical Assessment - Ehsan, Muhammad Asif (IJRDO- Journal of Educational Research, 2017)
Research involves a series of judicious and carefully executed activitiesthat enable the researcher to know how problems can be solved or at leastconsiderably minimized. Ergo, it embodies the processes of inquiry, investigation,examination and experimentation. These processes have to be carried outsystematically, diligently, critically, objectively and logically. The anticipated endresults help the researchers to deal with the problem. The paper dilates on theproposition that a problem does not necessarily mean that something is seriouslywrong with a current situation that needs to be rectified immediately. A problemcould simply indicate an interest in an issue where finding the right answers mighthelp to improve an existing situation. Methodology, on the other hand, is driven bycertain ontological and epistemological assumptions, and consists of researchquestions or hypotheses, a conceptual approach to a topic, the methods to be used inthe study and consequently the data sources. All of these components are inextricablylinked to one another in a logical manner. The paper canvasses quantitative andqualitative researches which constitute different approaches to social investigation.Various studies such as exploratory, descriptive and explanatory are discussed into thebargain.